The Wall and the Politics of Exclusion and Inclusion at Baja California Borderlands: A Pictorial Journey (Imaginations: Journal of Cross-Cultural Image Studies, 2022)
The essay considers the border wall between Mexico and the United States as its primary visual, symbolic, and material reference to reflect on the politics of exclusion and inclusion entangled in everyday discourses and practices in Baja California’s borderlands. Everyday bordering applies not only to governmental technologies of control but also to these sorts of politics. The essay proposes that the wall represents an exclusionary symbol that is nonetheless challenged by those who attempt to embed inclusion in this context. The pictorial journey shows aspects of common situations next to the wall between the Mexican cities of Mexicali and Tijuana.